Algorithms for connected word recognition a global approach - GROCHOLEWSKI, S. (Archives of Acoustics, 1991)
In this paper, which is basically a review, three approaches to the problem of recognizing word connected speech are presented. They all use the dynamic programming technique to solve the optimization problem which occurs in matching an unknown utterance against an artificially synthesized sequence of word templates. They are compared with regard to the computation time and the memory requirement.